PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA BENGKULU MITIGASI BENCANA BANJIR - Jumiati, Wira; Ledyawati (JURNAL ILMIAH IDEA, 2023)
This research aims to determine the implementation of the flood disaster mitigation program in the city of Bengkulu, researchers use qualitative methods, with a case study approach, research informants are determined using purposive sampling technique, where this technique is used if sample members are selected specifically based on the research objectives, The selection of informants was chosen deliberately, research data was collected through data collection techniques, namely observation, interviews, comments and document collection. Then it is analyzed through the stages of data reduction, data presentation, and drawing conclusions. Analysis of the research results was analyzed using Parsons’ Structural-Functionalism AGIL Theory. After discussing and analyzing the data obtained from research conducted regarding the Implementation of Flood Disaster Mitigation in Bengkulu City (Study at the Bengkulu City Regional Disaster Management Agency (BPBD). In an effort to implement disaster management, it is carried out through 3 (three) stages as follows: Program Pre-disaster The disaster prevention and mitigation stage is carried out to reduce and overcome the risk of disasters. The series of efforts carried out can be in the form of repairing and modifying the physical environment as well as raising awareness and increasing the ability to face the threat of disasters. Disaster program. The stages carried out when a disaster occurs, this is where the preparedness team comes in to immediately analyze and form an action plan. Post-disaster program. This stage is carried out to reduce the impacts and to prepare for subsequent disasters. After being analyzed using the Structural-Functionalism AGIL theory, the program implemented by the Bengkulu City BPBD is very relevant to the Structural-Functional AGIL theory. Parsons’ functionalism in planning and implementing Pre, During and Post flood disaster programs because it contains four elements of Structural-Functionalism theory, namely Adaptation, Goal Attachment, Integration and Latency